Pengaruh jumlah tumbukan pemadatan dan tingkat konsistensi aspal terhadap nilai modulus elastik campuran hot rolled asphalt - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
ABSTRACT In the project implementation of highway development, many flexible pavements with an asymmetrical gradation asphalt concrete such as Hot Rolled Asphalt (HRA) are apllied. In the asymmetrical gradation asphalt concrete, some of the middle sized grains decrease and cause the Voids in Mixed Aggregate (VMA) value greater than the closed gradation asphalt concrete. Beside that the main strength of an asymmetrical gradation asphalt concrete is in the mortar strength (the mixture of fine aggregate, filler and asphalt), whereas the coarse aggregate only functions as a filler. In this observation Hot Rolled Asphalt (HRA) was used as the object and variations in asphalt consistentcy level was also used (stated in asphalt penetration figure) i.e: (HRA)40 to Hot Rolled Asphalt mixture with AC 40- 50, (HRA)60 to Hot Rolled Asphalt mixture with AC 60-70 and (HRA)80 to Hot Rolled Asphalt mixture with AC 80-100 with variatons of the number of pounding 40, 50, 60, 70, 80, 90 and 100 times. The results of observation showed that the more number of compact pounding, the higher the asphalt consistentcy level and also the value of HRA (Sme) mixture elastic modulus and on the contrary . The value of Sme will show (HRA)40 > (HRA)60 > (HRA)80 in each number of the same compact